1999
DOI: 10.1046/j.1365-2435.1999.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tree growth rate, shoot size and foliar chemistry on the abundance and performance of a galling adelgid

Abstract: Summary 1.The abundance and performance of the Eastern Spruce Gall Adelgid, Adelges abietis, was evaluated on young, open-grown trees of White Spruce, Picea glauca, whose growth rates had been increased through fertilization or decreased through root-pruning. 2. In general, gall densities were highest on control trees and on mid-crown branches. Reduced galling success on fertilized trees was largely due to higher overwintering mortality of first-generation nymphs. Foliar magnesium, total tannin and total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
60
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 33 publications
14
60
0
Order By: Relevance
“…However, these results are similar to those reported by Craig et al (1999), who reported that Eurosta solidaginis (Diptera, Tephritidae) survival was highest on ramets with intermediate growth rates of Solidago altissima (Asteraceae). Our results also support the parabolic curves relationship reported by Mckinnon et al (1999) who found that Adelges abietis (Linnaeus, 1758) (Hemiptera, Adelgidae) gall abundance and density were higher on intermediate-sized trees and shoots of the white spruce Picea glauca (Moench) Voss (Pinaceae). Additionally, they speculated that A. abietis lacks the necessary resources for successful gall formation on smaller shoots and that it is unable to produce a stimulus strong enough to induce gall formation on large shoots.…”
Section: Discussionsupporting
confidence: 92%
“…However, these results are similar to those reported by Craig et al (1999), who reported that Eurosta solidaginis (Diptera, Tephritidae) survival was highest on ramets with intermediate growth rates of Solidago altissima (Asteraceae). Our results also support the parabolic curves relationship reported by Mckinnon et al (1999) who found that Adelges abietis (Linnaeus, 1758) (Hemiptera, Adelgidae) gall abundance and density were higher on intermediate-sized trees and shoots of the white spruce Picea glauca (Moench) Voss (Pinaceae). Additionally, they speculated that A. abietis lacks the necessary resources for successful gall formation on smaller shoots and that it is unable to produce a stimulus strong enough to induce gall formation on large shoots.…”
Section: Discussionsupporting
confidence: 92%
“…Larger galls also regulate the better survival rate of inducing insects (Abrahamson et al, 1989;Rehill and Schultz, 2001;Sopow and Quiring, 2001), because they have either more of or larger nutritive cells (Hartley, 1998). Alternatively, the optimal module-size hypothesis proposes that gall-inducing insect performance will be the greatest on intermediate-sized plant modules (McKinnon et al, 1999). This is based on the understanding that galls are induced by a dose-dependent stimulus from the insect (Sopow et al, 2003), and that a critical dose mass is necessary to induce a gall increase with module size (McKinnon et al, 1999).…”
Section: Parametersmentioning
confidence: 99%
“…Alternatively, the optimal module-size hypothesis proposes that gall-inducing insect performance will be the greatest on intermediate-sized plant modules (McKinnon et al, 1999). This is based on the understanding that galls are induced by a dose-dependent stimulus from the insect (Sopow et al, 2003), and that a critical dose mass is necessary to induce a gall increase with module size (McKinnon et al, 1999). The optimal module-size hypothesis proposes that galls are easily induced on smaller plant modules.…”
Section: Parametersmentioning
confidence: 99%
“…Whereas all endoparasites must be extremely finetuned to the internal environment of their host, gallers must also "take over" the development of a plant part and induce it to make a foreign structure, the gall. The growth rate or size of the plant module could influence both gall induction success (Bjorkman 1998;McKinnon et al 1999;Sopow et al 2003) as well as the fitness of juveniles in the developing gall (Craig et al 1989). The size of any particular plant part, such as a leaf, bud or shoot, varies not only among plants but also within them.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies with other gall insects have also reported variations in the relationships between the size of plant modules galled and the abundance or performance of gallers. Positive, negative, and parabolic relationships between plant module size and galler abundance or performance have resulted in numerous hypotheses (e.g., Bjorkman 1998;Larsson 1989;Larson and Whitham 1997;McKinnon et al 1999;Price 1991;Sopow et al 2003) that will not be discussed here.…”
Section: Introductionmentioning
confidence: 99%